B2C Marketing Strategies of Semiconductor Manufacturers: A Comparative Case Study of Memory and Non-Memory Companies' Social Media Promotion (aSSIST Business Review, 2026)
Background/Purpose: The semiconductor industry is undergoing intensifying competition in both memory and non-memory segments. While non-memory semiconductor companies such as NVIDIA, Intel, and Qualcomm have long pursued active B2C (Business-to-Consumer) marketing through social media, memory semiconductor companies including Samsung, SK Hynix, and Micron have historically remained passive in consumer-facing promotion. As the memory market transitions from price competition to technology competition—exemplified by High Bandwidth Memory (HBM) and Compute Express Link (CXL)—the question arises whether memory semiconductor companies should adopt active B2C marketing strategies comparable to their non-memory counterparts. Study Design/Methodology/Approach: This study employs a qualitative case study approach supplemented by a quantitative consumer survey (n=200). Social media presence across five platforms (X/Twitter, Facebook, Instagram, YouTube, LinkedIn) was systematically compared for three leading non-memory companies (NVIDIA, Intel, Qualcomm) and three leading memory companies (Samsung DS, SK Hynix, Micron). Follower counts and content strategies were analysed using data collected in November 2024; longitudinal follower trends for X and YouTube were tracked from January 2023 to December 2024 using Socialblade.com. A consumer survey was administered by Macromill Embrain from 4–6 December 2024 to 200 Korean adults aged 19–49 (150 male, 50 female), investigating the influence of advertising exposure on purchase decisions for Windows PCs, Android devices, and memory components (RAM/SSD). Findings: Non-memory semiconductor companies substantially outperform memory companies in social media follower counts across all platforms, and show significantly stronger follower growth on X and YouTube. Memory companies' social media exposure for RAM/SSD was less than half that of comparable device categories (42% vs. 86.5% for PCs; 81.5% for Android devices). However, among consumers who had been exposed to memory advertising and subsequently purchased RAM or SSD, 71.4% reported that the advertising influenced their purchase decision—a rate comparable to, and directionally higher than, the influence reported for Windows PC (62.2%) and Android device (67.0%) purchases. Originality/Value: This is the first systematic comparison of B2C social media marketing strategies across memory and non-memory semiconductor segments, combining platform-level analysis with consumer survey evidence. The findings demonstrate that active consumer promotion of memory semiconductors can positively influence purchase behaviour, providing empirical support for a strategic shift toward B2C marketing in the memory semiconductor sector. The study's implications extend beyond semiconductors to B2B industries more broadly.
Keywords: B2C marketing; B2B2C marketing; semiconductor industry; social media marketing; memory semiconductor; NVIDIA; Intel; Qualcomm; Samsung; SK Hynix; Micron; consumer promotion